[(2^7)^2x(2^2)^8+5^50:5^5-(7^16)^2]:[(8^5)^2+(5^3)^15-(7^4^2)^2]
Răspunsuri la întrebare
Răspuns de
3
[(2^7)^2x(2^2)^8+5^50:5^5-(7^16)^2]:[(8^5)^2+(5^3)15-(7^4^2)^2] =
= (2^14x2^16+5^(50-5)-7^32);[8^10+5^45-(7^16)^2] =
= (2^30+5^45-7^32):[(2^3)^10+5^45-7^32] =
= (2^30+5^45-7^32):(2^30+5^45-7^32) =
= 1
= (2^14x2^16+5^(50-5)-7^32);[8^10+5^45-(7^16)^2] =
= (2^30+5^45-7^32):[(2^3)^10+5^45-7^32] =
= (2^30+5^45-7^32):(2^30+5^45-7^32) =
= 1
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă